NORMATIVE JURIDICAL ANALYSIS OF THE POSITION OF GOVERNMENT REGULATION IN LIEU OF LAW (PERPPU) IN THE HIERARCHY OF STATUTORY REGULATIONS - Fitri Elfiani; Zulkifli; Nofrizal; Romadhan Lubis; Dearma Sinaga (RADJA PUBLIKA, 2025)
This study offers a normative and juridical analysis of the position of Government Regulations in Lieu of Law (Perppu) within the hierarchy of statutory regulations in Indonesia. It investigates the constitutional and legal framework surrounding Perppu, particularly in light of its